Parallel patterning of SiO2 wafer via near-field electrospinning of metallic salts and polymeric solution mixtures. (13th September 2017) - Hu, Sanyuan; Li, Heping; Su, Zhen; Yan, Youwei
Abstract: This paper describes a near-field electrospinning technique combined with heat treatment process used to directly align parallel metal oxide and metal nitride fibers on silicon dioxide substrate. The effects of near-field electrospinning parameters (including collector-to-needle distance, applied voltage and the moving speed of the collector) on the morphology of the resulted fibers have been studied. Metallic salt-contained precursor fibers are individually aligned via near-field electrospinning of metallic salts and polymeric solution mixtures. After applying calcination process to these well aligned precursor fibers, patterning by metal oxide and metal nitride fibers such as ZnO, Ga2 O3, TiO2, GaN and TiN is successfully obtained. The optical microscope images and the scanning electron microscopy show the presence of fiber patterns, whose crystalline structure is characterized by x-ray diffraction and Raman spectroscopy measurement. The results demonstrate the potential of this approach for assembling ceramic fibers into parallel arrays with controllable orientation and position.